EFFECTS OF BALLISTIC EXERCISES VERSUS PLYOMETRIC EXERCISES ON PERFORMANCE OF BADMINTON PLAYERS (Journal of Medical & Health Sciences Review, 2025)
Background: Badminton is a game performance that entails a combination of explosive force, agility and speed, hence very precise training interventions are necessary to instill the best performance of the game. The combination of ballistic and plyometric exercises is well-root in domain of development of the lower limbs strength and enhancing their reaction time and efficiency of dynamic movement, and the comparative impact on the results of playing badminton has not been investigated recently in close detail.Objective: The aim of the research was to compare the effect of the ballistic exercise with the plyometric exercise on indicators of competitive badminton players in terms of their performance.Design: The study is quasi experimental in which half of a dozen male and female badminton players (not having reached the age of 25 years) were randomly chosen into the ballistic and plyometric training groups. It was 8 weeks wherein the ballistic group went through medicine ball throwing exercises, kettlebell swings and jump squats or the plyometric group did not depth jumps, bounding, and lateral hops. These were the measured variables that showed before and after the intervention included the vertical jump height, the shuttle run time, the smash speed, and the time on agility T test. Data were analysed using paired and independent t-test with the level of significance, which was established at p < 0.05.Results: Both types of training resulted in the significant increase of all of the performance measures yet the performance of the group that underwent the training in the ballistic group had the improvements in the smash times (12.3% versus 8.5%) and the vertical jump (10.8% versus 7.9%) and in the plyometric group in agility (14.2% versus 11.1%). In the shuttle run time groups, there were not substantial interactions effects.Conclusion: it is evident that even badminton players can benefit through such training as ballistic and plyometrics exercises in improving performance; the training could definitely assist the badminton players in performing power-based movements whereas plyometrics would assist in developing agility.